Search for structurally diverse heterocyclic analogs as dual-acting antimalarial and antileishmanial agents: An overview - Faheem; Sanchita Dey; Samridhi Johri; M. Abirami; Banoth Karan Kumar; Donatella Taramelli; Nicoletta Basilico; Rafael Balana-Fouce; Kondapalli Venkata Gowri Chandra Sekhar; Sankaranarayanan Murugesan (Elsevier, 2022)
Infections caused by protozoan parasites continue to be a significant cause of morbidity and mortality across the globe, with malaria and leishmaniasis forming the fulcrum of these infections. Decreased effectiveness of existing drugs and increasing cases of drug resistance have called for a multifaceted approach for the development of safe, efficacious, and affordable drugs for malaria and leishmaniasis. The present review article aims to unearth structurally diverse compounds as dual-acting antimalarial and antileishmanial agents. The current review article mainly focuses on the structure, biological activities, and structure-activity relationship (SAR) studies of synthetic and natural compounds that showed promising potential against malaria and Leishmania parasites in the past decade (2011-2021).